2017
DOI: 10.1159/000454926
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Dependent Induction of Clr-b during Mouse Cytomegalovirus Infection Protects Bystander Cells from Natural Killer Cells via NKR-P1B-Mediated Inhibition

Abstract: Natural killer (NK) cells are innate lymphocytes that aid in self-nonself discrimination by recognizing cells undergoing pathological alterations. The NKR-P1B inhibitory receptor recognizes Clr-b, a self-encoded marker of cell health downregulated during viral infection. Here, we show that Clr-b loss during mouse cytomegalovirus (MCMV) infection is predicated by a loss of Clr-b (Clec2d) promoter activity and nascent transcripts, driven in part by MCMV ie3 (M122) activity. In contrast, uninfected bystander cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Hence, oncogenic Ras signaling downregulates Clr-b transcripts in a manner consistent with that previously observed following viral infection or genotoxic stress (9,(11)(12)(13)(14), perhaps indicative of an oncogenic stress pathway. To assess this effect at the Clec2d promoter level, a dualluciferase reporter assay (DLRA) was performed using the pGL3 vector harboring incremental fragments of the Clec2d promoter (100-500 bp upstream of transcriptional start site, TSS), and luciferase activity was measured relative to control Renilla luciferase activity in the presence of Ras G12V or Ras S17N cotransfection into NIH3T3 fibroblasts (12). Here, the activity of the 200 bp Clec2d fragment was significantly decreased by CA Ras G12V cotransfection relative to DN Ras S17N (Fig.…”
Section: Ras G12v Signaling Promotes a Loss Of Clec2d Nascent Transcrsupporting
confidence: 79%
See 2 more Smart Citations
“…Hence, oncogenic Ras signaling downregulates Clr-b transcripts in a manner consistent with that previously observed following viral infection or genotoxic stress (9,(11)(12)(13)(14), perhaps indicative of an oncogenic stress pathway. To assess this effect at the Clec2d promoter level, a dualluciferase reporter assay (DLRA) was performed using the pGL3 vector harboring incremental fragments of the Clec2d promoter (100-500 bp upstream of transcriptional start site, TSS), and luciferase activity was measured relative to control Renilla luciferase activity in the presence of Ras G12V or Ras S17N cotransfection into NIH3T3 fibroblasts (12). Here, the activity of the 200 bp Clec2d fragment was significantly decreased by CA Ras G12V cotransfection relative to DN Ras S17N (Fig.…”
Section: Ras G12v Signaling Promotes a Loss Of Clec2d Nascent Transcrsupporting
confidence: 79%
“…It was recently shown that Clr-b (Clec2d) promoter activity, nascent transcripts, and surface protein expression are downregulated in response to viral infection (9,(11)(12)(13), and that Clr-b transcripts are lost in response to genotoxic/cellular stress Figure 3. Ras G12V -mediated Clr-b loss requires MEK1, MEK2, and ERK2.…”
Section: Ras G12v Signaling Promotes a Loss Of Clec2d Nascent Transcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, the broadly expressed self Clr-b is recognized by the inhibitory NKR-P1B (115). MCMV infection leads to loss of Clr-b gene expression, in part by the activity of the viral m122 protein, which would be expected to yield an NK cell-activating signal (116,117). Recently, however, it was shown that cell surface-expressed m12 directly engages NKR-P1B, thereby suppressing NK cell effector activity in vitro and in vivo (118).…”
Section: Herpesvirus Nk Cell Evasion Strategiesmentioning
confidence: 99%
“…This process seems to engage an involvement of the interferons IFN-β and IFN-λs, respectively. Within the last years, Journal of Immunity has published many articles involving interferon signaling [9-13], emphasizing the important role of these inflammatory immune mediators in fighting viral infections. Future work will hopefully bring us the answer whether IFN-λs can be used as therapeutic target for the treatment of HIV infection.…”
mentioning
confidence: 99%